Sweet promised land. - Laxalt, Robert 1923- (Harper & Row, 1957)
A large print edition of the account a son writes of his father, an old Basque sheepherder who lived and worked in the American West for most of his life, who, in fulfilling his dream of returning to the Pyrenees, came to a new realization of what America meant to him.